Assessing health professionals' communication through role-play: an interactional analysis of simulated versus actual GP consultations - Atkins, Sarah (Sage, 2018)
Simulations, in which healthcare professionals are observed in dialogue with role-played patients, are widely used for assessing professional skills. Medical education research suggests simulations should be as authentic as possible, but there remains a lack of linguistic research into how far such settings authentically reproduce talk. This article presents an analysis of a corpus of general practice simulations in the UK, comparing this to a dataset of real-life GP consultations. Combining corpus linguistic and conversation analytic methodologies, key interactional features of the simulations are identified, particularly those associated with successful/unsuccessful performance in terms of the examiner’s grading. The corpus analysis identifies various forms of the phrase ‘tell me more about’ to occur significantly more frequently in the simulations compared to real GP consultations, typically in the opening sequences and most frequently in successful cases. It falls to a conversation analysis of the data, examining this phrase within the interactional context of these opening sequences, to better understand the actions it performs. Successful candidates in the simulations are found to perform a consistent sequential pattern, often incorporating this phrase. Though simulated, these interactions have real professional consequences for those being assessed. Linguistic findings about what constitutes successful interaction or differences to real-life practice therefore have important implications for professional education and assessment.